Effect of a standardised heart team protocol versus a guideline-based protocol on revascularisation decision stability in stable complex coronary artery disease: rationale and design of a randomised trial of cardiology specialists using historic cases - Yang Wang; Xi Li; Bo Xu; Zhe Zheng; Shen Lin; Hanping Ma (BMJ Open)
Introduction A multidisciplinary heart team approach has been recommended by revascularisation guidelines, but how to organise and implement the heart team in a standardised way has not been validated. Inter-team and intra-team decision instability existed in the guideline-based heart team protocol, and our standardised heart team protocol based on a mixed method study may improve decision stability. The objective of this study is to evaluate the effect of the standardised heart team protocol versus the guideline-based protocol on decision-making stability in stable complex coronary artery disease (CAD).Methods and analysis Eighty-four eligible interventional cardiologists, cardiac surgeons or non-interventional cardiologists from 26 hospitals in China have been enrolled. They will be randomised to a standardised heart team protocol group or a guideline-based protocol group to make revascularisation decisions for 480 historic cases (from a prospective registry) with stable complex CAD. In the standardised group, we will establish 12 heart teams based on an evidence-based protocol, including specialist selection, specialist training, team composition, team training and a standardised meeting process. In the guideline-based group, we will organise 12 heart teams according to the guideline principles, including team composition and standardised meeting process. The primary outcome is the overall percent agreement in revascularisation decisions between heart teams within a group. To demonstrate the clinical implication of decision-making stability, we will further explore the association between decision stability and 1-year clinical outcomes.Ethics and dissemination The study was approved by the Institutional Review Board (IRB) of Fuwai Hospital (No. 2019-1303). All participants have provided informed consent and all patients included as historic cases provided written informed consent at the time of entry to the prospective registry. The results of this trial will be disseminated through manuscript publication and national/international conferences, and reported in the trial registry entry.Trial registration number NCT05039567.